Rock and paleomagnetic data from two sediment cores from the Black Sea for the past 30 ka - Jiabo Liu; Norbert R Nowaczyk; Helge Wolfgang Arz (PANGAEA, 2022)
Rock magnetic and paleomagnetic results covering the past 30 ka were constructed from two sediment cores MSM33_856-1 (MSM33-55-1) and MSM33_855-1 (54-3) from the Black Sea. After the Mediterranean Sea water ingression, finely laminated organic-rich sapropelic sediments and coccolith oozes were deposited in the Black Sea since about 8.3 ka. Relict magnetic minerals in the Black Sea sarpoples are ferrous hemoilmenite, Fe-Mn and Fe-Cr spinels, and magnetite inclusions. In sediments deposited between about 14 and 8 ka, greigite and pyrite were formed in sediments because of the seawater penetration from overlying sediments after the seawater ingression. Before ~14 ka, the Black Sea sediments are dominated by detrital (titano-)magnetite minerals and the sporadically formed greigite which has SIRM/κLF ratios > 10 kAm-2. By comparison with detrital (titano-)magnetite samples between 20-30 ka, we found that relict magnetic mineral samples between 0-8.3 ka have similar behavior in recording the geomagnetic field. Moreover, the geomagnetic field variations reconstructed from the Black Sea sapropels are comparable with other validated regional datasets for the past 8.3 ka. The natural remanent magnetization (NRM) and the anhysteretic remanent magnetization (ARM) were measured with a 2G Enterprises 755 SRM (cryogenic) long-core magnetometer equipped with a sample holder for eight discrete samples at a separation of 20 cm. The magnetometer extquotesingles in-line tri-axial alternating field (AF) demagnetizer was used to demagnetize the NRM and ARM of the samples. The NRM was measured after application of AF peak amplitudes of 0, 5, 10, 15, 20, 30, 40, 50, 65, 80, and 100 mT. Directions of the characteristic remanent magnetization (ChRM) were determined by principle component analysis (PCA) according to Kirschvink (1980). The error range of the ChRM is given as the maximum angular deviation (MAD). The ARM was imparted along the samples extquotesingle z-axis with a static field of 0.05 mT and an AF field of 100 mT. Demagnetization then was performed in steps of 0, 10, 20, 30, 40, 50, 65, and 80 mT. The median destructive field of the ARM (MDFARM) was determined to estimate the coercivity of the sediments. The slope of NRM versus ARM of common demagnetization steps was used to determine the relative paleointensity (RPI). In most cases, demagnetization steps from 20 to 65 mT were used to determine the RPI.